Anatomija lesa za loke godal - Čufar, Katarina (Zbornik gozdarstva in lesarstva, 2007)
Four specimens of wood originating from string instrument bows or from the material intended to be used for the repair of bows were obtained from the string instrument workshop "Atelje Demšar". Foreign wood traders supplied the specimens under their commercial names: (1) pernambouc, (2) horse flesh, (3) brasil, and (4) snakewood. Macroscopic and microscopic wood anatomical investigations were carried out in order to verify the nomenclature of the traded specimens. The microscopic identification provided the following results: (1) Guilandina echinata (pernambouc, pau brazil, brazil), (2) Manilkara bidentata (massaranduba, horse flesh), (3) Shorea laevis (yellow balau, bangkirai), and (4) Brosimum guianense syn. Piratinera guianensis (snakewood). In three cases (1, 2 and 4), the trade names of the provided bow specimens were confirmed by wood anatomical identifications. In case 3, the wood anatomical features fully corresponded to timbers of the botanical species Shorea laevis (yellow balau, bangkirai) from Indomalaysia and not to Guilandina echinata or Caesalpinia spp. from South America. The identified wood species (1, 2 and 4) from South America are characterised by the following properties: fine and decorative texture, high density, good mechanical properties, brown or red coloured heartwood, good working properties (machinability and coating), and good dimensional stability. They are highly appreciated for string instrument bows. Among them, the wood of pernambouc is most valued. The wood of yellow balau, which is distinguished byinferior properties (e.g. excessive shrinkage), is not a typical wood for instrument bows. The fabrication of the bows, the properties of the investigated species and the importance of proper wood identification are presented as well.
Keywords: godalni lok; goslarstvo; les; struktura lesa